1986
DOI: 10.1177/0272431686064003
|View full text |Cite
|
Sign up to set email alerts
|

Individual Adjustment to School Transitions: An Exploration of the Role of Supportive Peer Relations

Abstract: Previous research has shown that the transition into junior high school can be difficult for certain subgroups, particularly girls. Recent work has also examined the social support roles played by best friends during the transition and found that high quality friendships can ease the adjustment to the new environment. The present longitudinal study of 410 students in a middle class suburban school district looked at adjustment to junior high school as a function of the quantity, frequency of contact, and intim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 16 publications
1
45
0
5
Order By: Relevance
“…Jones and Thornburg (1985) found no differences between students making either a sixth grade or seventh grade transition and students remaining in the same school. Finally, Fenzel and Blyth (1986) found no change in self-esteem fol-lowing the seventh grade transition to junior high school among students in their White, middle-class, suburban sample; Hirsch and Rapkin (1987) also reported no change in self-esteem between sixth grade and seventh grade despite a school transition. Although the lack of replication may be due in part to smaller sample sizes than those in the Blyth and Simmons work, differences in sample characteristics could also be responsible, along with unmeasured differences in secondary school environment and level of student preparation.…”
Section: Effects Of School Transitionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Jones and Thornburg (1985) found no differences between students making either a sixth grade or seventh grade transition and students remaining in the same school. Finally, Fenzel and Blyth (1986) found no change in self-esteem fol-lowing the seventh grade transition to junior high school among students in their White, middle-class, suburban sample; Hirsch and Rapkin (1987) also reported no change in self-esteem between sixth grade and seventh grade despite a school transition. Although the lack of replication may be due in part to smaller sample sizes than those in the Blyth and Simmons work, differences in sample characteristics could also be responsible, along with unmeasured differences in secondary school environment and level of student preparation.…”
Section: Effects Of School Transitionsmentioning
confidence: 85%
“…Although a limited effect, this pattern was consistent with the hypothesis of differential vulnerability to school transitions: Boys experiencing an early or double transition showed equal or better self-image than those experiencing a single, seventh grade transition; girls in these circumstances tended to show poorer self-image, especially relative to boys. The limited nature of the effect was not surprising given that such gender differences in vulnerability are not always found in suburban samples (Fenzel & Blyth, 1986;Jones & Thornburg, 1985). The relative lack of number and timing effects on self-image de-serves further comment.…”
Section: Gender Differences In Impactmentioning
confidence: 97%
“…Friendships may provide a secure relationship base from which to comfortably explore the new environment, and may foster greater competence and security in meeting transition challenges. Previous research has demonstrated that high quality friendships and peer acceptance prior to the junior high school transition were predictive of more positive self-esteem, social selfperceptions, school integration, and overall adjustment following the transition (Berndt, Hawkins, & Jian, 1999;Fenzel & Blyth, 1986;Wargo Aikins, Bierman, & Parker, 2005). In addition, being well-liked and popular with peers prior to the high school transition also appears to facilitate social adjustment across the high school transition (Cillessen & Mayeux, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Contingencies may be particularly salient during early adolescence given the normative increase in self-consciousness and the tendency to rely heavily on external feedback for selfworth (e.g., Harter 1999). In addition, adolescents may face a number of academic, social, and extracurricular stressors during the transition to middle and to high school (Fenzel and Blyth 1986;Hirsch and Rapkin 1987). Cambron and colleagues state that females experience a "double hit" in that they endure more negative events, and these events are often interpersonal in nature, a salient domain for female self-evaluation.…”
Section: Introductionmentioning
confidence: 99%